Theological Study of Power Ministry in the Community of Churches - Tonny Andrian (Journal of Asian Orientation in Theology, 2021)
The church is a legacy of the Kingdom of God which is owned by Jesus Christ, which also involves the participation of the Holy Spirit through believers of Jesus Christ as their Lord and Savior, where they serve one another in the unity of the Body of Christ, worship God through the worship of the people. believe, and proclaim the complete testimony of life and the gospel of Christ, the Kingdom of God (Evangelism) for the ecclesiastical community and the world. The church is a supernatural life, namely the existence of power, divine events as recorded in the Bible, so that church service is a powerful ministry, although often church services are natural and routine services. Thus the study of the theology of power ministry concerns the exegesis of the use of the words "power" and "energy", and the movement of the ministry of the Lord Jesus Christ, including the disciples who are always accompanied by demonstrations of Divine Power, including the essence of the Kingdom of God, which is related to the meaning of the salvation of His renewal, and the role The Holy Spirit who gives gifts of the Spirit based on the grace of the power of the grace of the Lord Jesus Christ. The study of this theological foundation is necessary so that the meaning of powerful ministry can be understood clearly, including its application in the life of the ecclesiastical community.